Tinzaparin vs. Nadroparin Safety and Efficacy in Neurosurgery - Florian Wilhelmy; Annika Hantsche; Michael Gaier; Johannes Kasper; Michael Karl Fehrenbach; Rene Oesemann; Jürgen Meixensberger; Dirk Lindner (MDPI AG, 2021)
Background: An outbreak of African swine fever (ASF) in China in 2020 has led to an unprecedented shortage of nadroparin. Most patients, especially those kept in hospital for surgery, are currently treated with prophylactic anticoagulation (AC). In search of alternatives for nadroparin (fraxiparine), we found no sufficient data on alternatives for neurosurgical patients, such as tinzaparin of European origin. We compared nadroparin and tinzaparin concerning adverse events (bleeding versus thromboembolic events) in neurosurgical patients. Methods: Between 2012 and 2018, 517 neurosurgical patients with benign and malignant brain tumors as well as 297 patients with subarachnoid hemorrhage (SAH) were treated in the Department of Neurosurgery, University Hospital Leipzig, receiving prophylactic anticoagulation within 48 h. In 2015, prophylactic anticoagulation was switched from nadroparin to tinzaparin throughout the university hospital. In a retrospective manner, the frequency and occurrence of adverse events (rebleeding and thromboembolic events) in connection with the substance used were analyzed. Statistical analysis was performed using Fisher's exact test and the chi-squared test. Results: Rebleeding rates were similar in both nadroparin and tinzaparin cohorts in patients being treated for meningioma, glioma, and SAH combined (8.8% vs. 10.3%). Accordingly, the rates of overall thromboembolic events were not significantly different (5.5% vs. 4.3%). The severity of rebleeding did not vary. There was no significant difference among subgroups when compared for deep vein thrombosis (DVT) or pulmonary embolism (PE). Conclusion: In this retrospective study, tinzaparin seems to be a safe alternative to nadroparin for AC in patients undergoing brain tumor surgery or suffering from SAH.